Endoplasmic reticulum stress could induce autophagy and apoptosis and enhance chemotherapy sensitivity in human esophageal cancer EC9706 cells by mediating PI3K/Akt/mTOR signaling pathway - Fang Zhou; Yan-Hua Li; Jian-Jun Wang; Jia Pan; Hong Lu (Tumor Biology, 2017)
The study was designed to explore the mechanism of tunicamycin-induced endoplasmic reticulum stress in human esophageal cancer EC9706 cells and EC109 cells, as well as its effects on cell autophagy, apoptosis, and chemoresistance. Tunicamycin-induced endoplasmic reticulum stress model was established in EC9706 and EC109 cell lines. Western blotting was employed to detect the expression of endoplasmic reticulum stress iconic protein GRP78. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used to evaluate the effect of different cisplatin and tunicamycin concentrations on survival rate of EC9706 cells and EC109 cells. Autophagy was monitored using monodansylcadaverin and apoptosis was detected by flow cytometry. Western blotting was used to detect the expressions of endoplasmic reticulum stress–related proteins (PERK, eIF2α, and CHOP), PI3K/Akt/mTOR signaling pathway–related proteins, autophagy-related proteins (LC3-I/LC3-II, Beclin-1, and p62), and apoptosis-related proteins (Bcl-2, Bax, and cleaved caspase-3). Tunicamycin led to increased expression of GRP78. With tunicamycin treatment, phosphorylation of PERK and eIF2α and CHOP expression increased. Meanwhile, the increase in cytolysosome was concentration and time dependent. With the increased tunicamycin concentration, there were increased expressions of Bax and cleaved caspase-3, decreased expression of Bcl-2, and lower phosphorylation of PI3K/Akt/mTOR signaling pathway–related proteins. Therefore, it can be concluded that the combination of tunicamycin and cisplatin could improve the sensitivity of EC9706 cells and EC109 cells to cisplatin; PI3K inhibitor BEZ235 could enhance cell autophagy and apoptosis and increase cell sensitivity to cisplatin.